L’essor du secteur de la santé annonce-t-il un modèle de développement anthropogénétique ? - Robert Boyer (Revue de la Régulation)
Why do health care costs growth faster than GDP? Away from a static equilibrium analysis, an evolutionary and institutionnalist approach stresses the coevolution of diseases, medical knowledge and techniques along with the financing availability and health care organization. In historical perspective, healthcare, coupled with education and culture, is going to draw an original mode of development, labelled as anthropogenetic. Based upon the development of human capabilities, it might delineate the socioeconomic regime of the end of the 21st century, both for the old industrial economies and the new countries acceding to development.